Alterations of the Plasma Peptidome Profiling in Colorectal Cancer Progression. Issue 4 (29th September 2015) - Bedin, Chiara; Crotti, Sara; Ragazzi, Eugenio; Pucciarelli, Salvatore; Agatea, Lisa; Tasciotti, Ennio; Ferrari, Mauro; Traldi, Pietro; Rizzolio, Flavio; Giordano, Antonio; Nitti, Donato; Agostini, Marco
Abstract : Early detection of colorectal cancer (CRC) remains a challenge. It has been highlighted that the pathological alterations within an organ and tissues might be reflected in serum or plasma proteomic/peptidic patterns. The aim of the study was to follow the changes in the plasma peptides associated to colorectal cancer progression by mass spectrometry. This study included 27 adenoma, 67 CRC (n = 33 I–II stage and n = 34 III–IV stage), 23 liver metastasis from CRC patients and 34 subjects disease‐free as controls. For plasma peptides analysis, samples purification was performed on the Nanoporous Silica Chips technology followed by matrix‐assisted laser desorption/ionisation‐time of flight analysis. Since the high complexity of the obtained dataset, multivariate statistical analysis, and discriminant pattern recognition were performed for study groups classification. Forty‐four of 88 ionic species were successfully identified as fragments of peptides and proteins physiologically circulating in the blood and belonging to immune and coagulation systems and inflammatory mediators. Many peptides clustered into sets of overlapping sequences with ladder‐like truncation clearly associated to proteolytic processes of both endo‐ and exoproteases activity. Comparing to controls, a different median ion intensity of the group‐type fragments distribution was observed. Moreover, the degradation pattern obtained by proteolytic cleavage was different into study groups. This pattern was specific and characteristic of each group: controls, colon tumour disease (including adenoma and CRC), and liver metastasis, revealing a role as biomarker in early diagnosis and prognosis. Our findings highlighted peculiar changes in protease activity characteristic of CRC progression from pre‐cancer lesion to metastatic disease. J. Cell. Physiol. 231: 915–925, 2016. © 2015 Wiley Periodicals, Inc.